INTEREST GROUP SESSION - MENTAL HEALTH PRACTICE AND AGING: HOLISTIC RECOVERY FROM MENTAL ILLNESS FOR OLDER VETERANS. (11th November 2018) - Muralidharan, A; Karel, M J
Abstract: Veterans with mental disorders are aging into older adulthood in unprecedented numbers. These individuals often present with complex care needs across physical, psychological, social, and cognitive domains. Innovative approaches targeted to the integrated healthcare needs of this group are required. This symposium will present data from Veterans Health Administration (VHA) junior investigators who are examining the holistic health care needs of this growing population, and developing and testing novel interventions and approaches to promote Veterans' holistic recovery. First, Amanda Peeples will present qualitative data from interviews with Vietnam era Veterans with posttraumatic stress disorder regarding their conceptualizations and beliefs about recovery. Next, Anjana Muralidharan will present on the development of a novel intervention in which VHA Peer Specialists, who themselves are Veterans with lived experiences with mental illness, promote participation in supervised fitness training among older Veterans with psychotic disorders. Finally, Christine Gould will present qualitative and quantitative feasibility data from a video-delivered relaxation intervention to treat anxiety disorders among older Veterans. Michele Karel, a geriatric mental health leader in the Office of Mental Health and Suicide Prevention in VA Central Office, will serve as discussant. She will comment on the importance of this work for supporting VHA and community providers alike in meeting the mental health needs of aging Veterans.